2013
DOI: 10.1097/pgp.0b013e318253c71b
|View full text |Cite
|
Sign up to set email alerts
|

Primary High-grade Serous Carcinoma Arising in the Urethra or Urethral Diverticulum

Abstract: Serous carcinomas most commonly arise within the uterine corpus or ovary/fallopian tube, but there are 2 prior case reports of primary vaginal serous carcinoma. We report 2 examples of high-grade serous carcinoma arising within the urethra or a urethral diverticulum (1 case each). Both neoplasms exhibited the classic morphologic features of high-grade serous carcinoma, and a combination of clinical, radiologic, and pathologic examination excluded other possible sites of primary neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Some authors [ 15 , 16 ] suggested that there is a clear association between clear cell adenocarcinoma and diverticula of the urethra and that CCAU is the most common malignancy arising from diverticula of the urethra. It has been stated whilst only 10% of carcinoma of the urethra is clear cell adenocarcinoma, one-third of such carcinomas originate in a diverticulum [ 15 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some authors [ 15 , 16 ] suggested that there is a clear association between clear cell adenocarcinoma and diverticula of the urethra and that CCAU is the most common malignancy arising from diverticula of the urethra. It has been stated whilst only 10% of carcinoma of the urethra is clear cell adenocarcinoma, one-third of such carcinomas originate in a diverticulum [ 15 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tumors arising from urethral diverticulum represent only 0.002% of female malignancies [4]. While different studies have found substantial variance, the vast majority of primary urethral cancer in either sex and any race is squamous cell carcinoma as it represents almost twice as many cases as transitional and adenocarcinoma combined [2, 4, 5]. Clear cell adenocarcinoma, however, has a clear association with diverticula and is the most common malignancy arising from them [1, 4].…”
Section: Discussionmentioning
confidence: 99%
“…However, these are rare lesions, representing only 0.002% of female malignancies, with *5% of female urethral carcinomas arising in a diverticulum. 69 Squamous cell carcinoma in situ has also arisen in a urethral diverticulum, in what the authors believed was the first reported case. 70 Due to the rarity of these lesions, there are no consensus protocols for therapy.…”
Section: Hellermentioning
confidence: 90%
“…This patient was also tumor free at 6 months. 69 A case of adenosquamous carcinoma arising in a villous adenoma in a 49-year-old woman has been reported. 54 The lesion presented as a rapidly growing painful mass with hematuria.…”
Section: Hellermentioning
confidence: 97%